La recepción del Petrarquismo en España a través de los comentaristas: hipótesis de trabajo - Hernández Esteban, María; López Suárez, Mercedes (Cuadernos de Filología Italiana, 2005)
Our aim is to continue the studies on the handwritten and printed copies of the Canzoniere in the Iberian Peninsula, paying special attention to the internal order of the compositions, not analyzed by previous critics. During the Renaissance, the important structural innovation accomplished by Petrarch in his book was not always appreciated nor respected: in different anthologies the metrical criterion was given priority over the original structure, which was then desintegrated, its adeguate transmission being consequently hindered. Most editions follow the Malatesta order, and from the Aldo edition in 1501 onwards the Vatican order is the most frequent. In the second Aldo edition the title of the second part was changed, focusing on the love story, and not on the moral and ethic reflexions of the author. It does not seem that the several commentators, whose diffusion in Spain has been very wide, although this question still deserves a serious study, have contributed to the transmission of the original and complete structure; neither Filelfo, nor Gesualdo, nor Vellutello thought that the order of the poems was due to Petrarch, so they felt free to introduce modifications, as Vellutello’ s tripartition.